TRANSESTERIFIKASI MINYAK KELAPA MENJADI BIODIESEL DENGAN KATALIS CAO DAN PENERAPAN BIODIESEL (B40) PADA ALAT FOGGING - Maria Stefani Bethan; Edy Supriyo (Gema Teknologi, 2021)
Biodiesel is a renewable fuel from a transesterification reaction in which triglycerides are converted into FAME with alcohol. Previous research proved that coconut oil can be used as biodiesel. This study aimed to determine the effect of temperature (40-60oC), catalyst concentration of CaO 2-5%w/w) and methanol (20-40%w/w) on the yield of biodiesel produced. The yield were then compared with the biodiesel specification from Pertamina, i.e. density, viscosity, acid number, flash point and cetane number. The result of present work showed that the transesterification reaction between coconut oil and methanol with CaO catalyst have got a reaction conversion of 75% at 60oC, for 2 hours. For producing biodisel, the optimum conditions were achieved when using methanol 20% w/w and a concentration of CaO 2% w/w. The specification biodiesel were as followed: density 836 kg/m3, viscosity 3.09 mm2/sec, acid number 0.37 mgKOH/gr, flash point 62oC, and Cetane value 50.5. In the application, biodiesel (B40) from coconut oil on a fogging machine with a noise of 81.5 dB.